Inculturation of Catholic Religion in Javanese Culture: A Study of Pilgrimage Tourism Experience in the Ganjuran Church, Bantul, Special Region of Yogyakarta - Rosmariani Manalu (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2022)
Most tourists visit Catholic pilgrimage tourism sites to 'pursue' holy water that is believed to cure disease and provide sustenance for them. This is what makes the miracle of holy water one of the unique attractions that play a role in shaping the tourist experience in various Catholic pilgrimage tourist attractions, including the pilgrimage tourism site of the Ganjuran Church complex. However, there is another special attraction that is so strong and prominent in the Ganjuran Church, namely the existence of forms of inculturation of Catholic religion in Javanese culture. This study aims to view and understand the role of the existence of forms of inculturation on the formation of tourist experiences in the Ganjuran Church. This study uses a qualitative descriptive approach, in which the data collected are types of qualitative data based on the results of in-depth interviews, field observations, photographs and literature. The result shows that the Ganjuran Church has several inculturative forms that have influenced tourism experiences starting from the temple, the inculturative panels of Way of the Cross, the Javanese church, the musical-instrumental gamelan, the Tirta Perwitasari holy water, the inculturative statues of Catholic saints and the Schmutzer hall. Align with these results , this study indicates that the existence of inculturation in the church has played a role in shaping various types of experiences, ranging from religious, cultural to recreational experiences.